A risk prediction model mediated by genes of APOD/APOC1/SQLE associates with prognosis in cervical cancer - Ya Zhang; Yuankun Qin; Danqing Li; Yingjie Yang (BMC, 2022)
Highlights Establishment and Validation of a risk model includes APOD, APOC1 and SQLE; APOD, APOC1 and SQLE are related to immunotherapy; APOD, APOC1 and SQLE associates with prognosis in cervical cancer